The "country-of-origin effect" in employee turnover intention: evidence from China - Ma, S.; Trigo, V. (International Journal of Human Resource Management, 2012)
The increasing presence of foreign direct investment in China has boosted the competition for talent among different multinational corporations (MNCs) from diverse national backgrounds. This article investigates the differences in the human resource management (HRM) approaches adopted by the US, European, and Japanese MNC subsidiaries operating in China and explores the relationships between employees' perceptions toward the HRM approaches and turnover intention. Significant differences in the HRM approaches and employees' level of turnover intention were found, indicating a 'country-of-origin effect' in HRM approaches that subsequently influences employees' attitudes. In addition, this article produces evidence suggesting that the perception of HRM characteristics predicts employees' intentions to quit. Implications for HRM convergence or divergence debate are discussed.